Peningkatan Produksi Tanaman Kentang (Solanum Tuberosum L.) Varietas Dayang Sumbi dengan Pemberian Aspirin dan Kompos Limbah Kubis (Brassica Oleraceae) - Rizal Hasan Harahap; Syahbudin Hasibuan; Abdul Rahman (Jurnal Ilmiah Pertanian ( JIPERTA), 2021)
This research was conducted using a factorial randomized block design (RBD) method, which consists of two treatment factors, namely: 1) Aspirin administration factor with growth inhibitors with a notation (A) consists of 4 levels of treatment, namely: A0 = Control (without administration) Aspirin); A1 = administration of Aspirin at a dose of 1.25 g / l of water; A2 = Giving Aspirin at a dose of 2.50 g / l water, 2) Factors for giving cabbage waste compost with a notation (K), consisting of 3 levels of treatment, namely: K0 = Control (without giving cabbage waste compost); K1 = Giving cabbage waste compost at a dose of 10 tons / ha; K2 = Giving cabbage waste compost at a dose of 20 tons / ha, each treatment was repeated 3 (three) times. The parameters observed in this study were plant height, number of leaves, leaf color, stem diameter, number of tubers and production weight. As for the results obtained from this study, namely: 1) Giving Aspirin has a very significant effect on plant height, number of leaves, number of tubers and weight of production, but no significant effect on leaf color and stem diameter; 2) Giving cabbage waste compost has a very significant effect on plant height, number of leaves, number of tubers and weight of production, but no significant effect on leaf color and stem diameter; and 3) The combination of aspirin and cabbage waste compost has a very significant effect on the number of tubers and production weight, but has no significant effect on plant height, number of leaves, leaf color and stem diameter.